Pemahaman Orang Tua terhadap Toilet Training dalam Meningkatkan Kemandirian Anak di RA Al-Huda 1 Sukatani Purwakarta - Putri, Regina; Wulandari, Hayani (Jurnal Ilmiah Wahana Pendidikan, 2024)
Implementing toilet training is one option to increase children's independent attitudes which needs to be implemented by parents. This research aims to determine parents' understanding of toilet training to increase children's independence at RA Al-Huda 1 Sukatani Purwakarta. The research method used was descriptive qualitative with sample of 20 people. The sampling applied was Saturated Sampling (Non-probability sampling). In this research, a checklist questionnaire was used as an instrument. From the research results, it can be concluded that parents' understanding of toilet training to increase children's independence is "Sufficient Understanding" with a total score of 40%